Responsabilidade Social e Universidade: uma ação necessária - Ligia de Carvalho Abões Vercelli (EccoS – Revista Científica)
In recent years the subject of the Social Responsibility assumed place of prominence in the professional formation offered by the universities, therefore they ahead have an ethical commitment of the existing social problems in our society. In the university it is prioritized research and education, that is, the formal education, and little value is given to the extension however, we understand that it is by means of the extensionistas projects saw education not-deed of division, that the community where it is inserted will know so that and for who the university is the service. Thus, to involve the faculty and learning in social projects became prerequisite in the construction of solid professional abilities to understand the problems presented for the Brazilian context. Of this form, this article has for objective to reflect on the thematic Social Responsibility in the university by means of extensionistas projects. For this, we break of the origin of the Social Responsibility Entrepreneur and College student, we appraise the term under the optics of different authors stops later establishing the relation Social Responsibility and university.